The Role of Media in Domestic Violence - Okoli , Basil Chuka; Ngwube, Arinze (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Domestic violence is widespread and shows no signs of lessening in Nigeria and women have been victims of physical or sexual violence committed by a previous husband. Common forms of violence against women in Nigeria are rape, acid attacks, molestation, wife beating, and corporal punishment. Media can play a lead role in the society’s fight against violence against women. As media is the eye, ear and limbs of the society they could help a great deal in mitigating violence against women. Based on this, the study examines the impact of the media in the fight against domestic violence among women and girls in Yola North Local Government Area of Adamawa State. The objectives of the includes to identify the nature of domestic violence among girls in Yola North Local Government Area of Adamawa State, identify the role of the media in the fight against domestic violence among women and girls Yola North Local Government Area of Adamawa State, find out means to enhance the role of the media in the fight against domestic violence among women and girls Yola North Local Government Area of Adamawa State. The research design adopted in this study was descriptive survey design. The method of data collection was Key Informant Interview (KII). The question guide titled Domestic Violence Questionnaire (DVQ) was used to gather the required data. The data collected were analysed using qualitative content analysis. The study discovered that media could also provide a platform for key influencers (celebrities, politicians, sports-people, women groups etc) to publicly challenge violence. Media has been a useful way to expose abuse wherever it happens, and for women and men across the world to come and disclosing information is a vital tool in this fight. With right information, women became substantially more willing to report incidents of VAW to authorities and agents of the state. Moreover, men and women became more likely to believe that their fellow community members would intervene to stop VAW. To effectively address the problem of this form of domestic violence in Nigeria, the media have to brace up to the task of uncovering cases of domestic violence by husbands, brothers, in-laws, gangs/boys, sects, etc. and following up such cases in the court of law, intensifying effort at awareness creation, giving prominence to the reportage of cases of domestic violence, devoting special page for discussion of domestic violence (in the case of print media), organizing debates on the issue to enlighten the public about the incidence of violations of the rights of women and the girl-child, carrying out in-depth analyses of issues concerning domestic violence, use of improved surveillance system such as the closed circuit system installed in strategic places such as the parks, churches, markets, schools and other public places, alerting government of any possible outbreak of violence among others.